A historiografia da matemática no século XVIII: a escrita da história das matemáticas por Jean Etienne Montucla e o contexto francês - Santos, Arnaldo Aragão (2016)
The study undertaken consists of a proposal for reflection on the Jean Etienne Montucla’s work, History of Mathematics, written in the mid-eighteenth century. In this sense, based on analysis of documents, approaches have been developed within the spheres of analysis in the history of science. Although intriguing, the particularities of the writing in History of Mathematics have not been treated enough by their historians who, by the way, barely discuss about their approaches and intentions before the twentieth century. To contextualize the work of Montucla, permeated by the French editorial development, specially the contemporary encyclopaedic genre and secularization of intellectual activities of his time, we seek to contribute to the research on the History of Mathematics and its historiography to seek connections that can be established between the historical development of mathematical knowledge and his writing. In this order, in an attempt to revisit the work of Montucla, we gather efforts to locate her before their relations and intellectual motivations of the mid-eighteenth century.